Efektivitas Penggunaan Metode Amaba dalam Kemampuan Bertilawah untuk Siswa dengan Hambatan Pendengaran - Rahma, Raya Isnindi (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
The ability to read the newspaper is also needed by students with hearing, now there are many supporting learning of the newspaper for children with hearing hearing one method that will be used as an amaba method. This research method uses the method of Amaba in the knowledge of children with hearing impairments. The assessment used is a quantitative review with A single subject design research type assessing A-B-A. Research methods that show the method of amaba in the ability to speak for students with hearing, improve the ability to speak using the method of amaba